Application of the Business Judgment Rule in the Responsibility of the Board of Directors of State-Owned Enterprises: the Case Of Business Cooperation (KSU) and the Acquisition of PT Jembatan Nusantara (JN) by PT ASDP - Serlika Aprita; Rizadatul Qolbun; Dian Puspa Iwari; Evy Febryani (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study discusses the application of the Business Judgment Rule (BJR) in the responsibilities of directors of State-Owned Enterprises (BUMN) by emphasizing that the directors have a strategic position as a company organ that is fully responsible for the management of the company as regulated in the BUMN Law and the Limited Liability Company Law. Through a normative juridical research method with a statutory approach, a conceptual approach, and a literature study, this study analyzes the extent to which the BJR doctrine can provide legal protection for directors when business decisions taken cause losses or are considered detrimental to state finances. The results of the study indicate that the BJR is an important instrument to ensure that directors are not immediately burdened with responsibility as long as business decisions are taken based on good faith, the principle of prudence, and do not exceedauthority, and based on adequate information. This study also found that the different characteristics of SOEs as business entities and bearers of public mandates often cause the implementation of BJR to clash with the paradigm of state losses, creating legal uncertainty for directors. Therefore, consistent implementation of BJR is necessary to provide proportional legal protection and encourage SOE directors to carry out business functions professionally without fear of criminalization of decision-making